Victorian travellers, Apennine landscapes and the development of cultural heritage in eastern Liguria, c. 1875-1914 - Balzaretti, Ross (Wiley, 2011)
This article, which focuses on Italian Apennine landscapes in the northern region of Liguria, investigates late nineteenth-century travel from the perspective of historical ecology. It argues that travellers' observations and reflections can be rich sources for landscape history, and that travel writing is therefore a worthwhile source for ecologists. However, travel writing was a conflicted genre torn between such realistic visions of landscape and more common aesthetic ones, as contemporary views of the perceived picturesqueness of coastal Liguria demonstrate. Historians of travel have been much more interested in 'aesthetic travellers'. in part because the meaning of travel for identity construction is a more fashionable topic among historians tha ecology. Policymakers at both UNESCO and the EU have unfortunately espoused a visions of 'cultural landscape' based on aesthetics. Instead a more precise understanding of how past societies created landscapes through practice is essential if these are to be maintained in the future.